A novel meniscal root refixation pull‐in technique with an all‐suture anchor shows biomechanical properties comparable to standard suture anchor and transtibial pull‐out techniques - Thorben Briese; Amaris Kieninger; Christian Peez; Adrian Deichsel; Elmar Herbst; Maurice Balke; Michael J. Raschke; Christoph Kittl (Journal of Experimental Orthopaedics)
Abstract Purpose Repair techniques for posterior meniscal root (PMMR) tears include repair with transtibial pull‐out and anchors. An alternative approach uses all‐suture anchors pulled in, avoiding a posterior medial portal. While clinical feasibility has been assessed, biomechanical properties of this technique remain unknown. We hypothesised that the biomechanical properties using the pull‐in technique would be comparable to those achieved with conventional repair techniques. Methods Fifty fresh‐frozen porcine tibiae were fixed in a steel pot. Whereas in group (1) the native meniscal root was kept intact (native meniscal root (NM)), the PMMR was sectioned and refixed in groups (2)–(5): (2) Double‐loaded suture anchor (screw anchor) (SA), (3) transtibial pull‐out repair with two sutures (TTPO), (4) double‐loaded pull‐in repair with all‐suture anchor that was pulled into the subcortical bone which was predrilled from retrograde direction (PULL) and (5) double‐loaded push‐in repair with all‐suture anchor traditionally pushed into the predrilled subcortical bone in antegrade direction (PUSH). Testing was performed using a universal testing machine with 1000 cycles (5–20 N/0.5 Hz) with subsequent load‐to‐failure (LTF) meaning failure of the NM or refixation. Outcomes measured included LTF (N), cyclic displacement (mm), and stiffness (N/mm). The failure mode was documented macroscopically. Study design Controlled laboratory study. Results No repair technique restored the stability of the NM, reaching 1064.6 ± 226.0 N in LTF (p ≤ 0.0001). Reconstructions had significantly lower LTF: SA (251.4 ± 52.8 N), TTPO (233.4 ± 50.0 N), PULL (206.2 ± 86.5 N) and PUSH (214.3 ± 55.2 N). The NM showed the highest stiffness with 156.1 ± 76.3 N/mm (p ≤ .0001) compared to (SA) 36.2 ± 10.1 N/mm, (TTPO) 33.6 ± 6.2 N/mm, (PULL) 36.8 ± 12.7 N/mm, (PUSH) 27.7 ± 6.6 N/mm. Increased displacement after 1000 cycles was shown, with (2.3 ± 0.7 mm) in PULL, only with significant differences noted between NM (1.5 ± 0.8 mm) and PUSH (3.1 ± 0.7 mm) (p ≤ .001), NM and SA (2.5 ± 0.8 mm) (p ≤ .05), and TTPO (2.1 ± 0.7 mm) and PUSH (p ≤ .05). No failures occurred during cyclic loading. Failure after LTF was always a suture cut‐out at the meniscus. Conclusion Current repair techniques for posterior medial root tears do not fully restore the biomechanical properties of an intact root. The new pull‐in technique with an all‐suture anchor which is pulled in instead of pushed in shows biomechanical properties comparable to conventional methods, especially regarding LTF. Level of Evidence There is no level of evidence as this study was an experimental laboratory study.